The Characteristics and Functions of SSRs and SNPs Based on the Transcriptome of Tuta absoluta Exposed to Different Concentrations of Abamectin and Chlorantraniliprole - Fanxue Zhang; Meimei Mu; Zonglin Wang; Haoran Zhang; Yilan Song; Rong Xiao (Insects)
Tuta absoluta (Meyrick) is an important invasive pest that seriously affects the yield and quality of tomatoes. In this study, based on the previously obtained transcriptome data, a total of 25,123 SSR loci and 332,537 SNP loci were identified. The identified SSRs had occurrence and appearance frequencies of 28.62% and 40.60%, respectively. SSRs with a length equal to or greater than 12 bp constituted 58.25% of the total SSR loci. Through the analysis of GO, COG annotations, and the KEGG pathway database, it was revealed that the majority of SSR-transcripts were involved in fundamental cellular metabolic functions. In addition, the frequency of SNP occurrence was approximately one SNP locus per 175 base pairs (bp), and the transition type was the main variant type. The functional annotations of SNP-transcripts were primarily concentrated in biological synthesis pathways such as peroxisome, RNA transport, carbon metabolism, and protein processing in the endoplasmic reticulum. These synthesis pathways are involved in the detoxification mechanism of T. absoluta and contribute to its enhanced survival under pesticide susceptibility. These findings provide valuable data for constructing genetic maps, assessing genetic diversity, and determining functional orientation in insects, and they also provide basic data for the molecular mechanism of T. absoluta ‘s response to pesticide susceptibility.